221k views
0 votes
Given the sequence in the table below, determine the sigma notation of the sum for term 4 through term 15.

n an
1 4
2 −12
3 36

User Effbiae
by
6.0k points

2 Answers

3 votes


\bf \begin{array}ll \cline{1-2} n&a_n\\ \cline{1-2} 1&4\\ &\\ 2&\stackrel{4(-3)}{-12}\\ &\\ 3&\stackrel{-12(-3)}{36}\\ \cline{1-2} \end{array}\qquad \impliedby \textit{common ratio of


\bf \qquad \qquad \textit{sum of a finite geometric sequence} \\\\ S_n=\sum\limits_(i=1)^(n)\ a_1\cdot r^(i-1)\implies S_n=a_1\left( \cfrac{1-r^n}{1-r} \right)\quad \begin{cases} n=n^(th)\ term\\ a_1=\textit{first term's value}\\ r=\textit{common ratio}\\[-0.5em] \hrulefill\\ r=-3\\ a_1=4\\ n=15 \end{cases} \\\\\\ S_(15)\implies \displaystyle\sum\limits_(i=4)^(15)~4(-3)^(i-1)

User Krishnom
by
4.6k points
4 votes

Answer:


\sum_(n=4)^(15)4(-3)^(n-1)

Explanation:

The given sequence is 4, -12, 36

We can see there is a common ratio


(a_(2) )/(a_(1) ) =
(-12)/(4)=(-3)


(a_(2) )/(a_(3) ) =
(36)/(-12)=(-3)

Therefore, the given sequence is a geometric sequence.

Now we have to determine the sigma notation of the sum for term 4 through term 15.

Since explicit formula of the sigma can be represented as


T_(n)=a(r)^(n-1)

where
T_(n) = nth term

a = first term

n = number of term term

r = common ratio

and sum is denoted by
\sum_(n=1)^(n)a(r)^(n-1)

Now for the given sequence sigma notation will be


\sum_(n=4)^(15)4(-3)^(n-1)

User Smartrahat
by
5.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.